The implementation of the mobile application “Colorectal Leakage App”, based on the Dutch Leakage Score, for early detection of anastomotic leakage after colorectal surgeries—pilot study - Meiram Mamlin; Saule Khamzina; Gulden Zhanmukanbetova; Nurlan Mukazhanov; Aidana Amangeldiyeva; Arman Kozhakhmetov (Frontiers in Surgery)
BackgroundColorectal cancer is the third most common malignancy globally and in Kazakhstan, with anastomotic leakage (AL) being a severe complication of colorectal surgeries. Early detection of AL is critical for improving patient outcomes and reducing mortality, as the condition is also characterized by a deterioration in quality of life. The “Colorectal Leakage App,” based on the Dutch Leakage Score (DLS), offers a standardized approach for postoperative monitoring and early AL detection.MethodsIn this single-center pilot study conducted at the National Research Oncology Center in Kazakhstan, sixty-three patients who underwent colorectal surgery were monitored daily during the postoperative period using the “Colorectal Leakage App” mobile application. Patients with anastomosis were included. The app integrates clinical signs and laboratory data to recommend further diagnostic steps, such as CT with rectal contrast. The primary endpoint was to determine the feasibility of using the “Colorectal Leakage App” in standardized postoperative care. The frequency of AL was also measured as an additional outcome.ResultsOf 63 patients enrolled, AL was observed in 3.2% (2/63) of cases. In one case, the app flagged a score of 9 on postoperative day (POD) 7, prompting timely CT and intervention. Another case was identified via drainage findings on POD 5. A third flagged case (score 10, POD 10) revealed a gallbladder abscess rather than AL, highlighting the app’s potential for broader complication monitoring.DiscussionThe “Colorectal Leakage App,” based on the Dutch Leakage Score, was integrated as a standardized postoperative care protocol. Given the small sample size and insufficient number of AL cases, statistical analysis is currently not feasible. However, initial results suggest that the application may have a role in enhancing postoperative surveillance.ConclusionThe implementation of the “Colorectal Leakage App” may facilitate the early detection of AL. In this single-center pilot study, the AL rate was 3.2% (2 out of 63 patients). We plan to continue our study and conduct a multicenter study to further evaluate the app's effectiveness across different healthcare settings in Kazakhstan, aiming to standardize postoperative care.